The Power Of Jesus Christ's Teaching Methods - Lanny Laras; Daniel Tumbel (Jurnal Didaskalia, 2022)
Learning and learning is very important in the educational process that involves teachers and students or teachers and students. Edward and Frances Simpson in their paper "Principle of Biblical Teaching and Learning" edited by Werner C. Graendorf in his book entitled Introduction Christian Education, put forward ten laws of teaching and learning.